Analysis of Consumer Personal Data Protection for Data Integration: the Gojek-Tokopedia Case - Anisya Humaira; Kukuh Tejomurti (Universitas Muhammadiyah Tangerang, 2022)
This research aims to analyze the regulation of personal data protection and legal protection of consumer personal data from two tech giants, Gojek and Tokopedia, which officialy announced the acquisition on May 17, 2021. PT GoTo Gojek Tokopedia combines e-commerce, on demand, financial services and financial services. This research is a normative or doctrinal research with statue approach, a conceptual approach, and a case approach. The sources of legal materials used are primary and secondary legal materials. In Indonesia, there is no rigid law governing personal data protection because the regulation of personal data protection in Indonesia is currently still sectoral. In the terms of GoTo Group service users, consumer personal data settings are regulated in the privacy policies of Gojek and Tokopedia. Data integration after the acquisition of PT. Tokopedia by PT. APlikasi Karya Anak Bangsa raises new if there is a data leak and or use of consumer data without the consent of the data owner